Dissociated Role of D-Serine in Extinction During Consolidation vs. Reconsolidation of Context Conditioned Fear - Inoue, Ran; Talukdar, Gourango; Takao, Keizo; Miyakawa, Tsuyoshi; Mori, Hisashi (Frontiers in Molecular Neuroscience, 2018)
Extinction-based exposure therapy is widely used for the treatment of anxiety disorders, such as post-traumatic stress disorder (PTSD). D-Serine, an endogenous co-agonist at the glycine-binding site of the N-methyl-D-aspartate-type glutamate receptor (NMDAR), has been shown to be involved in extinction of fear memory. Recent findings suggest that the length of time between the initial learning and an extinction session is a determinant of neural mechanism involved in fear extinction. However, how D-serine is involved in extinction of fear memory at different timings remains unclear. In the present study, we investigated the role of D-serine in immediate, delayed, and post-retrieval extinction of contextual fear memory using wild-type and serine racemase (SRR) knockout (KO) mice that exhibit 90% reduction in D-serine content in the hippocampus. We found that SRR disruption impairs post-retrieval extinction, facilitates immediate extinction, but has no effect on delayed extinction of contextual fear memories. The impaired post-retrieval extinction of contextual fear memory in SRRKO mice was associated with reduced expression of the GluA1 subunit of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-type glutamate receptor (AMPAR) in the hippocampal synaptic membrane fraction after post-retrieval extinction, and this reduction of AMPAR and impaired post-retrieval extinction were rescued by the administration of D-serine to SRRKO mice. Our findings suggest that D-serine is differentially involved in the regulation of contextual fear extinction depending on the timing of behavioral intervention, and that combining D-serine or other drugs, enhancing the NMDAR function, with post-retrieval extinction may achieve optimal outcomes for the treatment of PTSD.